Shaping of the Public Policy Culture in Lithuania: Sociological Exploration of Change in Environmental Policy and Public Participation - Rinkevičius, Leonardas (Sociologija. Mintis ir veiksmas, 2006)
This paper aims at diagnosing change in policy culture in Central and Eastern Europe, particularly Lithuania, focusing on the field of environmental policy. The article analyzes public participation in the Soviet period, the years of break down of the Soviet system, and contrasts it with social change during the years of transition to a market economy and democratization of society. Based on interviews with relevant actors, secondary data analysis, and discourse analysis, this paper illuminates the shift of public involvement in environmental science and technology policy to a different mode. This shift, or dialectics of policy culture, is epitomized by a changing mode of citizen participation – from latent forms and “double faced” culture in the Soviet times towards euphoria about civic democratic governance and direct participation during the years of “Singing revolution”, and towards another round of colonization of public policy by the bureaucratic domain and the private sector during the 1990s.
Keywords: public policy; environmental policy; policy culture; social change